PKR downregulation prevents neurodegeneration and β-amyloid production in a thiamine-deficient model - Mouton-Liger, F (Cell Death Dis, 2015)
Brain thiamine homeostasis has an important role in energy metabolism and displays reduced activity in Alzheimer's disease (AD). Thiamine deficiency (TD) induces regionally specific neuronal death in the animal and human brains associated with a mild chronic impairment of oxidative metabolism. These features make the TD model amenable to investigate the cellular mechanisms of neurodegeneration. Once activated by various cellular stresses, including oxidative stress, PKR acts as a pro-apoptotic kinase and negatively controls the protein translation leading to an increase of BACE1 translation. In this study, we used a mouse TD model to assess the involvement of PKR in neuronal death and the molecular mechanisms of AD. Our results showed that the TD model activates the PKR-eIF2α pathway, increases the BACE1 expression levels of Aβ in specific thalamus nuclei and induces motor deficits and neurodegeneration. These effects are reversed by PKR downregulation (using a specific inhibitor or in PKR knockout mice).